Hello healthcare: evaluating the impact of a healthcare conference for secondary school pupils - Nadin Hawwash; Jacqueline Lavallee; Enam Haque (BMC Medical Education)
Abstract Background There are over 350 careers within healthcare. However, in the United Kingdom, opportunities are limited for secondary school pupils to learn about a variety of healthcare careers. We aimed to address this by delivering an in-person regional conference on healthcare careers for Year 10 pupils from widening participation (WP) backgrounds. This “Hello Healthcare Conference” enabled pupils to gain insight into a range of careers within healthcare. We explored the impact of the conference on pupils’ self-reported knowledge, skills, and attitudes to healthcare careers. Methods We conducted a pre-test-post-test study of 44 pupils from WP backgrounds who attended Hello Healthcare to evaluate the effectiveness of the conference. A five-point Likert scale confidence questionnaire was used to evaluate the impact of Hello Healthcare on school pupils’ self-reported knowledge, skills, and attitude to healthcare careers. A Shapiro-Wilk test revealed a lack of normal distribution (p < 0.05); therefore, the pre-test-post-test results for each pupil were compared using a Wilcoxon signed-rank test. Results 44 Year 10 pupils from WP backgrounds across 4 schools were included in this study. Self-reported knowledge of most healthcare careers improved after the conference. Pupils’ perception of having the necessary skills for a healthcare career significantly increased, with Z = -5.78, p < 0.001, and large effect size (r = -0.87). Pupils’ perception that they could successfully apply for a healthcare course increased (Z = -5.52, p < 0.001, r =-0.83). Conclusions The Hello Healthcare conference was beneficial in improving pupils’ awareness and attitudes towards healthcare careers and demonstrated an effective method by which to address the limited perceived knowledge WP pupils may have. Government and universities need to support and invest in the Hello Healthcare conference concept to replicate the impact of the intervention in other regions of the UK.